PERANCANGAN APLIKASI E-COMMERCE BERBASIS M-COMMERCE (MOBILE COMMERCE) - Eri Bayu Pratama (Universitas Bina Sarana Informatika, 2013)
M-commerce (mobile commerce) is the buying and selling system which is carried out through mobile devices (mobile phone) that are connected to the Internet. M-commerce is the next generation of e-commerce, which has the delivery of information in the trade, through mobile devices (mobile phone). In designing this application of research methods used are planning, analysis, design and implementation of the program temporarily. The design of this application was made to provide other alternatives in delivering and receiving information for users in the trade.Key words: m-commerce, mobile devices